2022
DOI: 10.1177/15910199221138140
|View full text |Cite
|
Sign up to set email alerts
|

Overall cerebral small vessel disease burden is associated with outcome of acute ischemic stroke after mechanical thrombectomy

Abstract: Objectives To investigate the association between the overall cerebral small vessel disease (CSVD) burden and the therapeutic outcome of mechanical thrombectomy (MT) in patients with acute anterior circulation large-vessel occlusion stroke. Materials and Methods Data of patients who achieved successful revascularization after MT for acute anterior circulation large-vessel occlusion stroke in the Ningbo Medical Center Lihuili Hospital between April 2017 and January 2022 were retrospectively analyzed. The overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In addition, our study showed that a high CSVD burden not only increased the risk of rapid IGR, but also correlated with higher rates of stroke progression and poor functional outcomes at 3 months. The association between CSVD burden and stroke outcomes remains controversial [4,6,31]. Our findings highlight the need for a more comprehensive assessment of CSVD in stroke patients, as it could serve as a potential prognostic factor and guide treatment decisions.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In addition, our study showed that a high CSVD burden not only increased the risk of rapid IGR, but also correlated with higher rates of stroke progression and poor functional outcomes at 3 months. The association between CSVD burden and stroke outcomes remains controversial [4,6,31]. Our findings highlight the need for a more comprehensive assessment of CSVD in stroke patients, as it could serve as a potential prognostic factor and guide treatment decisions.…”
Section: Discussionmentioning
confidence: 86%
“…Cerebral small vessel disease (CSVD) represents a group of pathological features affecting intracranial arterioles, venules, and capillaries that can cause lacunes, white matter hyperintensities (WMH), cerebral microbleeds (CMB), and enlarged perivascular spaces (EPVSs) on neuroimaging [1,2]. Recently, emerging evidence has indicated that CSVD burden increased the worse prognosis in acute ischemic stroke patients with endovascular treatment (EVT) [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%